Vivências de crianças filhas de catadores de materiais recicláveis: implicações para enfermagem - Rodrigues, Ana Eliza Belizario (2017)
Citing recyclable materials is a widespread practice in low-income populations. This practice is considered the only way to guarantee the generation of income and the supply of basic needs to these families. Although this activity has an environmental importance, the subjects involved are faced with adversities during this practice, such as excessive exposure to risks, violence, invisibility, social exclusion, as well as discrimination and high levels of stress. Faced with this reality, are inserted children who live in these families and who end up becoming vulnerable in this context. It is understood that healthy child development is related to several factors, and the experiences, experiences in the environment and family play a mediating role between the child and society, being an essential element for child development. Thus, this study has the object and objective of describing the daily experiences of children living in families of collectors of recyclable materials. The research was developed with families who work on collecting recyclable materials that have children and / or children under their responsibility from the age of six to 12 years. Data collection took place through interviews with family members mediated by the genogram and ecomap and with the children interviews mediated by the toy. The research scenarios were constituted in the space of the Recyclers Associations of the municipality of Santa Maria / RS and in the domicile of some of the families involved in this activity. Fifteen families of recyclers and 27 children between the ages of 6 and 12 participated in the study. The analysis of the data occurred through the French Discourse Analysis (AD). In the genogram and ecomap of the families, a strong characteristic is observed, which would be single-parent families, being exclusively carried out by women, thus assuming the head of the household, as well as remade family nuclei. The experience of these children, daughters of collectors of recyclable materials revealed themselves in two odd ways. The first is the perception of these children around environmental issues and the other would be the ludic universe, permeated by games and games. These two perceptions weave the experiences of these children, revealing immeasurable dimensions of possibilities and creativity that surround these everyday, making them potent for their development. However, the families studied here represent a part of the reality of families living in the peripheries of this country. They are people who live with poor health conditions, who survive with the minimum and who transform this minimum at maximum daily. In this way, themes such as these need to be disseminated in the academic circles, so that their specificities and needs are heard by the public authorities, through wide dissemination. I hope this study will instigate further research, because there is still much to be researched, questions to be answered and voices to be heard.